Tinjauan Kinetika Kimia Daya Hambat Minyak Daun Cengkeh (Syzygium aromaticum) dan Hasil Mikroenkapsulasinya Terhadap Eschericia coli - Nurliana, Laily -; Kurniawati, Desi; Musta, Rustam; Abdul Kadir, Laode; Dewi, Fitria; Nurjana, Siti (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2020)
The secondary metabolite compounds contained in clove leaves oil have the potential to be antibacterial Escherichia coli. The kinetic analysis is based on the inhibition zone formed as a result of the inhibition of clove leaves oil and the results of microencapsulation on E. coli bacteria. The determination of the inhibition zone uses the disk diffusion method by using amoxicillin as a positive control and tween oil as a negative control. The kinetic review is intended to find out the antibacterial inhibitory reaction process by determining the reaction order (n), rate constant (k) as well as the At-Ao-t relationship of clove leaves oil and the results of its microencapsulation. Based on the research results obtained by the reaction order (n) of clove oil as an antibacterial E. coli is n = 0.1913; with the rate constant k = 5.7679. The reaction order (n) results of microencapsulation as antibacterial E. coli are 0.5039; with the rate constant k = 4.7323.